Mechanisms for preserving archaeological areas, a case study of the archaeological site of Zemmouri el-Bahri, Boumerdes - Bediar, Adel; Sahli, Fayçal; Alal, Ahmed; Dehimi, Salim (Technium Social Sciences Journal, 2022)
Cultural heritage expresses the identity and privacy of the previous societies, as it represents great importance to researchers in this field, and countries have taken steps to preserve it through legislative and technical mechanisms and procedures represented in protection schemes, and Algeria was among the first countries in protecting its archaeological sites, especially after the issuance of Law 04/1994 related to the protection of cultural heritage, Which gave a strong impetus in defining and protecting these sites, and the archaeological site of Zammouri al-Bahri is considered among the very important sites, as it includes several periods of time from prehistoric times to the present time, passing through the Roman and Islamic periods, this study came according to two stages, the first stage was the use of a georadar device to detect the boundaries of the site, and the second stage was the diagnosis and the most important appropriate solutions to treat the deterioration.